XRD Identification of Ore Minerals during Cruises: Refinement of Extraction Procedure with Sodium Acetate Buffer - Milinovic, Jelena; Dias, Ágata; Janeiro, Ana I.; Pereira, Manuel F. C.; Martins, Sofia; Petersen, Sven; Barriga, Fernando J. A. S. (Minerals, 2020)
The on-board identification of ore minerals during a cruise is often postponed until long after the cruise is over. During the M127 cruise, 21 cores with deep-seafloor sediments were recovered in the Trans-Atlantic Geotraverse (TAG) field along the Mid Atlantic Ridge (MAR). Sediments were analyzed on-board for physicochemical properties such as lightness (L*), pH and Eh. Selected samples were studied for mineral composition by X-ray powder diffraction (XRD). Based on XRD data, sediment samples were separated into high-, low- and non-carbonated. Removal of carbonates is a common technique in mineralogical studies in which HCl is used as the extraction agent. In the present study, sequential extraction was performed with sodium acetate buffer (pH 5.0) to remove carbonates. The ratio between the highest calcite XRD reflection in the original samples (Iorig) vs its XRD-reflection in samples after their treatment with the buffer (Itreat) was used as a quantitative parameter of calcite removal, as well as to identify minor minerals in carbonated samples (when Iorig/Itreat > 24). It was found that the lightness parameter (L*) showed a positive correlation with calcite XRD reflection in selected TAG samples, and this could be applied to the preliminary on-board determination of extraction steps with acetate buffer (pH 5.0) in carbonated sediment samples. The most abundant minerals detected in carbonated samples were quartz and Al- and Fe-rich clays. Other silicates were also detected (e.g., calcic plagioclase, montmorillonite, nontronite). In non-carbonated samples, Fe oxides and hydroxides (goethite and hematite, respectively) were detected. Pyrite was the dominant hydrothermal mineral and Cu sulfides (chalcopyrite, covellite) and hydrothermal Mn oxides (birnessite and todorokite) were mineral phases identified in few samples, whereas paratacamite was detected in the top 20 cm of the core. The present study demonstrates that portable XRD analysis makes it possible to characterize mineralogy at cored sites, in particular in both low- and high-carbonated samples, before the end of most cruises, thus enabling the quick modification of exploration strategies in light of new information as it becomes available in near-real time.
7 citations (Crossref) [2022-09-21]

Variability of the hydrothermal fields within the Portuguese seafloor (MAR) - Dias, Ágata; Relvas, J.M.S.Relvas; Marques, A. F.; Qiu, Wenhong; Barriga, F J A S; Ribeiro, L; Calado, A

Trace-element compositions of sulfides from inactive Tianzuo hydrothermal field, Southwest Indian Ridge: Implications for ultramafic rocks hosting mineralization - Ding, Teng; Wang, Jia; Tao, Chunhui; Dias, Ágata Alveirinho; Liang, Jin; Wang, Yuan; Chen, Jie; Wu, Bin; Huang, Hui (Ore Geology Reviews, 2022)
The recently explored inactive Tianzuo hydrothermal field, in the amagmatic segment of the ultraslow-spreading Southwest Indian Ridge (SWIR), is closely associated with detachment faults. In this site, sulfide minerals are hosted by serpentine-bearing ultramafic rocks and include high-temperature (isocubanite, sphalerite, and minor pyrrhotite) and low-temperature (pyrite I, marcasite, pyrite II, and covellite) phases. In this study, trace-element concentrations of isocubanite and pyrite II were used to elucidate mineralization processes in ultramafic rocks hosting sulfides. Results show that isocubanite is enriched in metals such as Cu, Co, Sn, Te, Zn, Se, Pb, Bi, Cd, Ag, In, and Mn, and pyrite II is enriched in Mo and Tl. The marked enrichment in Te, Cu, Co, and In in isocubanite (compared with Se, Zn, Ni, and Sn, respectively) is most likely due to the contribution of magmatic fluids from gabbroic intrusions beneath the hydrothermal field. The intrusion of gabbroic magmas would have enhanced serpentinization reactions and provided a relatively oxidizing environment through the dissolution of anhydrite precipitated previously in the reaction zone, within high temperature and low pH conditions. This might have facilitated the extraction of metals by initial hydrothermal fluids, leading to the general enrichment of most metals in isocubanite. Metals in pyrite II have compositions similar to those of isocubanite, except for strong depletion in magmatically derived Te, Cu, Co, and In. This means that serpentinization processes had a dominating role in pyrite II precipitation as well. The enrichment of pyrite II in Mo and Tl is also indicative of seawater contribution in its composition. The study concludes that serpentinization reactions contribute effectively both to high- and low-temperature sulfide mineralization at Tianzuo hydrothermal field, with gabbroic intrusions further promoting high-temperature sulfide mineralization, providing additional metals, fluids and heat. In contrast, low-temperature sulfide mineralization occurred during the cooling of gabbroic intrusions, with decreasing rates of serpentinization reactions and a significant influence of seawater.
Keywords: SWIR; Serpentinization; Sulfide; Tianzuo; Trace-element; Ultramafic rocks

The evolution of sulfur isotope in hydrothermal fluids along the formation of chimney of Menez Gwen (MAR): mineralization implications - Qiu, W; Dias, Ágata; Costa, Isabel Maria Amaral; Barriga, F

Surface sediment composition and distribution of hydrothermal derived elements at the Duanqiao-1 hydrothermal field, Southwest Indian Ridge - Dias, Ágata; Liao, Shili; Tao, Chunhui; Su, Xin; Yang, Zhen; Ni, Jianyu; Liang, Jin; Yang, Weifang; Liu, Jia; Li, Wei; Dong, Chuanwan (Marine Geology, 2019)
9 citations (Crossref) [2022-09-21]

Sulphide mineralization in Arctic seafloor hydrothermal fields: extending the European exploration area to the Far North - Cruz, M I; Dias, Ágata; Pedersen, R B; Relvas, J M R S; Fonseca, R; Barriga, F J A S (2013)

Sulfur isotopic compositions of sulfides along the Southwest Indian Ridge: implications for mineralization in ultramafic rocks - Dias, Ágata; Ding, Teng; Tao, Chunhui; Liang, Jin; Chen, Jie; Wu, Bin; Ma, Dongsheng; Zhang, Rongqing; Wang, Jia; Liao, Shili; Wang, Yuan; Yang, Weifang; et al. (Mineralium Deposita, 2020)
11 citations (Crossref) [2022-09-21]

Sulfide Sites in the Arctic Ocean: Jan Mayen and Loki’s Castle, Mineralogical Magazine - Cruz, M I; Marques, A F; Dias, Ágata; Pedersen, R; Relvas, J M R S; Barriga, F J A S (2013)

Sulfide mineralization of the Saldanha hydrothermal field (MAR): constraints from sulfur isotope in-situ microanalysis - Dias, Ágata; Qiu, W; Barriga, F; Tao, C (2019)

Sub-Seafloor Sulfide Mineralization in the Saldanha Hydrothermal Field, Mid-Atlantic Ridge (MAR) - Dias, Ágata; Qiu, Wenhong; Barriga, Fernando J A S; Tao, Chunhui (Goldschmidt Abstracts, 2020)
0 citations (Crossref) [2022-09-21]

Sr and Nd isotopic composition of Jan Mayen and Loki’s Castle: a progress report - Cruz, M I; Marques, F A M; Dias, Ágata; Pedersen, R; Barriga, F (2014)

Serpentinization and its implications for ultramafic-hosted sulfide mineralization: A case study at the Tianzuo hydrothermal field, 63.5°E, Southwest Indian Ridge - Ding, Teng; Dias, Ágata Alveirinho; Wang, Jia; Tan, Tingting; Liang, Jin; Wu, Bin; Tao, Chunhui (Marine Geology, 2023)
Reaction of ultramafic rocks with seawater and subsequent serpentinization has been considered one of the most important factors controlling the formation of ultramafic-hosted seafloor massive sulfide (UM-SMS) deposits. However, the mineralization processes responsible for these deposits remain poorly understood, in particular because they are less abundant as compared with their basaltic counterparts. In this work, serpentinites with different alteration grades collected at the Tianzuo hydrothermal field (THF), Southwest Indian Ridge, were studied. Mineralogical and chemical analyses were performed in the secondary opaque minerals resulting from serpentinization to understand the role of this process during the formation of UM-SMS deposits. Our results show that these opaque minerals mainly consist of magnetite, hematite, pentlandite, and minor pyrite, suggestive of high but varying oxygen and sulfur fugacities. The hematite is characterized by an enrichment in Mg, Si, Ni, and Co as compared with magnetite. Pentlandite associated with hematite has elevated and consistent Ni contents as compared with that associated with magnetite. These results indicate that breakdown and decomposition of primary silicate and sulfide minerals during serpentinization has controlled the sources of ore-forming materials. Concentrations of Te are variable and show a positive correlation with Ni in pentlandite associated with magnetite or hematite, suggesting that gabbroic intrusions provided additional material to the hydrothermal system. Oxidation and sulfidation conditions are ideal for the formation of trisulfur ion S3− in THF, which can significantly improve the capability of hydrothermal fluids for leaching ore-forming metals from the wall rocks, promoting the formation of THF. In addition of reduced systems, hydrothermal fluids with high oxygen and sulfur fugacities triggered by extensive seawater infiltration can most likely also develop in ultramafic-hosted systems. These results suggest that the areas with well-developed fractures are promising candidates for further exploration of UM-SMS deposits along mid-oceanic ridges.
0 citations (Crossref) [2022-12-25]
Keywords: Opaque minerals; Oxidation and sulfidation; Sulfide mineralization; Tianzuo hydrothermal field; Ultramafic rocks

Saldanha hydrothermal field: the role of the sediment-cover in the preservation of ore-forming minerals - Dias, Ágata; Barriga, F (2015)

Resource estimation of the sulfide-rich deposits of the Yuhuang-1 hydrothermal field on the ultraslow-spreading Southwest Indian Ridge - Yu, Junyu; Tao, Chunhui; Liao, Shili; Dias, Ágata; Liang, Jin; Yang, Weifang; Zhu, Chuanwei (Ore Geology Reviews, 2021)
Seafloor massive sulfide (SMS) deposits are important deep-sea mineral resources expected to occur predominantly on slow- and ultraslow-spreading mid-ocean ridges. Resource estimates are already available for some of the largest SMS deposits on slow-spreading ridges but not on ultraslow-spreading ridges. Based on geological mapping and sampling, this study investigates the distribution and content of sulfide-rich deposits in the Yuhuang-1 hydrothermal field (YHF), located on the ultraslow-spreading Southwest Indian Ridge. The sulfide-rich deposits in the YHF are composed of two areas ∼500 m apart: the southwest sulfide area (SWS) and the northeast sulfide area (NES). We calculated the volume of sulfide-rich mounds in the YHF and arrived at a total accumulation of ∼10.6 × 106 tons, including at least ∼7.5 × 105 tons of copper and zinc and ∼18 tons of gold. Furthermore, considering the coverage of layered hydrothermal sediment mixed with sulfide-rich breccias, which may have underlying massive sulfide deposits, the maximum total mass was estimated at ∼45.1 × 106 tons. This suggests that the YHF is one of the largest SMS deposits worldwide and confirm that ultraslow-spreading ridges have the greatest potential to form large-scale SMS deposits.
3 citations (Crossref) [2022-09-21]
Keywords: Resource estimate; Seafloor massive sulfide deposits; Southwest Indian Ridge; Yuhuang-1 hydrothermal field

Research Projects: Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Petrology and geochemistry of the igneous rocks from Macao (South China) :tectono-magmatic implications - Quelhas, Pedro Moniz (University of Saint Joseph; Universidade de Lisboa. Faculdade de Ciências, 2019)
The territory of Macao is composed of several granitic intrusions belonging to one of the biggest granite provinces in the world, the Southeast China Magmatic Belt (SCMB), located in the southeast (SE) area of the Cathaysia Block. The SCMB is known by the occurrence of large volumes of Mesozoic magmatic rocks (over 90% are granitic rocks and equivalent volcanic rocks with minor basalts), occupying a total outcrop area of nearly 200.000 km2. The geology of Macao (~30 Km2) is dominated by granitic rocks displaying a wide range of textural, mineralogical and chemical features, making it an ideal region to study these rocks and the petrogenetic processes responsible for their diversity. This study employed a wide range of research methodologies, namely field studies, petrography, zircon geochronology, mineral chemistry, whole-rock elemental and isotopic geochemistry to determine the nature of the source, the petrogenetic processes and the tectonic regimes of the Mesozoic magmatism in this region. Thus, the data collected along this study aims to provide new knowledge on the tectono-magmatic evolution of Macao, in particular, and of SE China, in general. The results obtained from the high-precision U–Pb zircon geochronology, acquired through isotope dilution thermal ionization mass spectrometry (ID-TIMS) and in-situ laser ablation multi-collector inductively coupled mass spectrometry (LA-MC-ICPMS), revealed different ages for Macao granites. Despite its relatively small area, the determined ages tightly constrain the Macao granitic magmatism to two periods, ranging from 164.5 ± 0.6 to 162.9 ± 0.7 Ma (MGI – Macao Group I granites) and 156.6 ± 0.2 to 155.5 ± 0.8 Ma (MGII – Macao Group II granites). In addition, younger dacitic rocks were dated at 150.6 ± 0.6 Ma and <120 Ma. The existence of two proximal but distinct granitic pulses, spanning for a time of about 9 Ma and separated by ca. 6 Ma, in the Macao granitic suite suggests that it was incrementally assembled. This hypothesis is also extendable to the neighbouring Hong Kong region, where the magmatic activity occurred in four major pulses spanning for about 24 Ma. However, the MGII granites indicate the occurrence, on the Pearl River Delta region, of a magmatic pulse between those defined in Hong Kong at the origin of Lamma Suite (165–160 Ma) and the Kwai Chung Suite (148–146 Ma). In addition, Rare Element Earth (REE) ratios suggest that this pulse may only occur in Macao area, while MGI granites show evolving trends of REE ratios similar to those of Jurassic granites outcropping in vast areas of the Cathaysia Block (SE China). Inheritance patterns in the zircon U–Pb data indicate the presence of a population of antecrysts (165–180 Ma) crystallized from earlier magmatic pulses and a population of inherited zircons, from Precambrian to Phanerozoic sources, incorporated into the magmas during melting and/or ascent/emplacement at crustal levels. The oldest inherited ages (2.4 Ga and possibly 2.9 Ga) suggest contribution of Proterozoic and possibly of late Archaean crustal sources for the Macao magmatism. The granitic rocks of Macao are mainly high-K calc-alkaline metaluminous to weakly peraluminous I-type granites with variable degrees of fractionation. Fractional crystallization played an important role in the evolution of these granites, though the fractionation paths differ for the highly fractionated facies of both groups mainly due to distinct accessory fractionating phases. Such difference is evident by distinct REE evolution trends: while MGI magmas seem to have evolved by gradual enrichment in heavy REE relatively to light REE, originating progressively flatter REE patterns, magmas from MGII are marked by depletion of middle REE, leading to progressively concave upward REE patterns. However, while most of the geochemical variation of the MGII granites can be explained by fractional crystallization, the same is not true for MGI granites. The MGI highly fractionated granites show evidence for the REE tetrad effect and are characterized by non-CHArge-and-RAdius-Controlled (non-CHARAC) behaviour of trace elements, suggesting late-stage melt/fluid interactions involving F-rich fluids. The stage of evolution represented by the MGI highly fractionated granites corresponds to the onset of fluid/melt interaction in a highly evolved granitic system, which may have led to enhanced hydrothermal activity in more evolved stages, as those represented in neighbouring areas in SE China. Significant differences in isotopic composition were also observed, with the MGII being characterized by a much narrow range of initial 87Sr/86Sr ratios and εNd(t) and εHf(t) values than MGI. Based on these differences, the MGII granites are considered to be part of a comagmatic suite that has evolved in closed system, contrasting with what can be inferred for MGI. The increase in initial 87Sr/86Sr ratios with degree of evolution, the presence of metasedimentary enclaves and the high percentage of inherited zircon with Paleozoic ages in MGI, suggest the occurrence of an assimilation fractionation crystallization (AFC) process. The AFC processes were a major cause for the I-S transitional characteristics of the MGI highly fractionated granites and possibly of the other similar Jurassic biotite granites in SE China. The observed decoupling of Sr, Nd and Hf isotope systems might have resulted from magma mixing between the granitic and more mafic magmas, which caused the homogenization of Sr isotope ratios but not of the Nd and Hf ones. Such process is also supported by the occurrence of Microgranular Mafic Enclaves (MME) hosted by the granites. Isotope and major element compositions together with model ages strongly suggest that Macao granitic magmas were generated by partial melting of infracrustal medium-to-high K basaltic Paleo-Proterozoic to Mesoproterozoic protoliths heated by, and mixed to some degree with mantle-derived magmas. The temporal and spatial association of Macao and SE China Jurassic I-type granites with basaltic/gabbroic rocks, syenites and A-type granites, displaying typical intraplate chemical features, indicates an extensional regime rather than an active margin for the origin of these rocks. It also points to an important role of mantle-derived magmas in the production of SE China Jurassic granites. Adiabatic decompression melting of the asthenospheric mantle produced mafic magmas, which underplated at the base of the crust (Moho), subsequently triggering partial melting of the lower crust to generate the granitic magmas. The Jurassic Macao granites are interpreted as being produced in an intraplate extensional setting related to the break-off and foundering of a previously flat-slab (Paleo-Pacific plate) beneath the Eurasian plate. The boundary between east and west Cathaysia blocks is roughly along the Zhenghe-Dapu Fault (ZDF), which intersects the SE China coast near Hong Kong and is thought to have played a major role for the Mesozoic magmatic activity in this region. The stronger isotopic affinities of Macao granites with the other granitic rocks and lower crustal xenoliths from the western Cathaysia Block suggest that the ZDF is likely to pass south of Macao, a fact that has not been mentioned before. In addition to the Early Yanshanian (Jurassic) granitic magmatism in Macao, the younger ages obtained for the dacite dykes indicate that the territory was also affected, to a lesser degree, by Late Yanshanian (Cretaceous) magmatism. The transition from granitic to dacitic magmatism most likely corresponds to a change in the regional tectonic regime, which induced a significant change in the magma genesis processes. In contrast with the intraplate features of Macao and SE China Jurassic granites and coeval mafic rocks, the geochemical features of the Macao dacite dykes (e.g. high LILE/HFSE ratios and negative anomalies of Nb, Ta and Ti) are identical to those characterizing arc-like subduction-related magmas. These dacites are most likely evolved products of arc-like magmatism and may testify the reestablishment of a normal subduction system in this area of SE China.
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2016)

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Petrology and Geochemistry of Granitic Rocks from Macao - Dias, Ágata; Quelhas, P; Lou, U; Mata, J; Ribeiro, M L (2016)

Oxyhydroxide Hydrothermal Crusts from Saldanha Hydrothermal Field - Costa, Pedro; Dias, Ágata (Goldschmidt Abstracts, 2020)
0 citations (Crossref) [2022-09-21]

Ore-Forming Process of the Menez Gwen Hydrothermal Field: In situ S Isotopes and Trace Metals Constraints - Dias, Ágata; Qiu, Wenhong; Costa, Isabel Maria Amaral; Barriga, Fernando J A S (Goldschmidt Abstracts, 2020)
0 citations (Crossref) [2022-09-21]

Occurrence and precipitation mechanism of silver in pyrite from chimney fragments in the Edmond hydrothermal field, Central Indian Ridge - Zhang, Huichao; Chen, Kean; Tao, Chunhui; Alveirinho Dias, Ágata; Liang, Jin; Yang, Weifang; Liao, Shili; An, Fang; Yin, Bohao; Sun, Chuanqiang (Ore Geology Reviews, 2023)

New geochemical constraints on I-type granites of Macao: evidences for fractional crystallization and petrogenetic affinities with Jurassic-Cretaceous granites in SE China - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Borges, R; Ribeiro, M. L (2017)

Mesozoic Granitic Magmatism in Macao, Southeast China - Quelhas, P. M.; Mata, J.; Lou, U. T.; Ribeiro, M. L.; Dias, Ágata (AGU Fall Meeting Abstracts, 2016)
Macao ( 30 Km2) is a territory characterized by small granitic intrusions, located along the coastal region of Southeast China (Cathaysia Block). Granitoids occur as different facies, including microgranite dykes, with distinct textural, mineralogical and geochemical features, for which a middle-upper Jurassic age ( 164 Ma) has been proposed. New data suggest that these granitoids are mostly high-K calc-alkaline metaluminous (A/CNK = 0.8 - 1.1) biotite granites, consistent with total absence of primary muscovite. They show variable amounts of SiO2 (67-77%), reflecting different degrees of magmatic evolution. There is also variability in terms of trace elements, particularly Rare Earth Elements (REEs), evidenced by decreasing (La/Sm)N, (Gd/Lu)N, (Ce/Yb)N and (Eu/Eu*)N towards the more evolved samples, which can be partly attributed to fractional crystallization processes. Most of the granitoids are characterized by (La/Yb)N = 3 - 10.8, showing negative Ba, Nb, Sr, Zr, P, Ti and Eu anomalies. On the other hand, microgranite dykes, along with a few more evolved granites, show an opposite tendency, being usually enriched in HREEs relatively to LREEs with (La/Yb)N = 0.4 - 1.1. Our data suggests intermediate genetic affinities between I-type and A-type granites. Although these granitoids are mostly metaluminous (characteristic of I-types), Ga/Al ratios, usually used to identify A-types, are close to the accepted boundary between A-type and other granite types. The affinities with A-type granites are more marked for the more evolved facies, which depict higher values of FeOt/MgO (14 - 60) and K2O/MgO (60 - 250). Their trace element characteristics are also transitional between WPG (Within-plate granites) and Syn-COLG (Collision Granites). We interpret those transitional characteristics (A/I and WPG/Syn-COLG) of Macao granitoids as reflecting an origin by melting of infracrustal sources over a period of high heat transfer from mantle to crust during an extensional tectonic setting probably contemporaneous with the subduction of the paleo-Pacific plate beneath the Eurasia, whose paleo-suture is thought to be located in the east flank of the Central Range, Taiwan.
Keywords: 8499 General or miscellaneous; VOLCANOLOGY

Material Source of Sediments from West Clarion–Clipperton Zone (Pacific): Evidence from Rare Earth Element Geochemistry and Clay Minerals Compositions - Qiu, Zhongrong; Tao, Chunhui; Ma, Weilin; Dias, Ágata Alveirinho; Hu, Siyi; Shao, Yuexiao; Yang, Kehong; Zhang, Weiyan (Journal of Marine Science and Engineering, 2022)
The geochemistry and mineralogy of sediments provide relevant information for the understanding of the origin and metallogenic mechanism of ferromanganese nodules and crusts. At present, there are still few studies on the sediment origin of the Clarion–Clipperton Zone (CCZ) of the east Pacific, particularly on the systematic origin of sediments with a longer history/length. Here, bulk sediment geochemistry and clay mineral compositions were analyzed on a 5.7 m gravity core (GC04) obtained at the CCZ, an area rich in polymetallic nodules. The results indicate that the average total content of rare earth elements (REE), including yttrium (REY), in sediments is 454.7 ppm and the REEs distribution patterns normalized by the North American Shale Composite of samples are highly consistent, with all showing negative Ce anomalies and more obvious enrichment in heavy REE (HREE) than that of light REE (LREE). Montmorillonite/illite ratio, discriminant functions and smear slide identification indicate multiple origins for the material, and are strongly influenced by contributions from marine biomass, while terrestrial materials, seamount basalts and their alteration products and authigenic source also make certain contributions. The REY characteristics of the sediments in the study area are different from those of marginal oceanic and back-arc basins, and more similar to pelagic deep-sea sediments. Based on LREE/HREE-1/δCe and LREE/HREE-Y/Ho diagrams, we conclude that samples from the study area had pelagic sedimentary properties which suffered from a strong “seawater effect”.
Number: 8 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Clarion–Clipperton Zone; material source; rare earth elements; sediments geochemistry

Magmatic Evolution of Garnet-Bearing Highly Fractionated Granitic Rocks from Macao, Southeast China: Implications for Granite-Related Mineralization Processes - Quelhas, Pedro; Mata, João; Dias, Ágata (Journal of Earth Science, 2021)
The widespread W-(Mo)-Sn-Nb-Ta polymetallic mineralization in Southeast (SE) China is genetically associated with Mesozoic highly fractionated granitic rocks. Such rocks have enigmatic mineralogical and geochemical features, making its petrogenesis an intensely debated topic. To better understand the underlying magma evolution processes, petrography, garnet chemistry and whole-rock major and trace element data are reported for Jurassic highly fractionated granitic rocks and associated microgranite and aplitepegmatite dikes from Macao and compared with coeval similar granitic rocks from nearby areas in SE China. Despite the fact that the most evolved rocks in Macao are garnet-bearing aplite-pegmatite dikes, the existence of coeval two-mica and garnet-bearing biotite and muscovite granites displaying more evolved compositions (e.g, lower Zr/Hf ratios) indicates that the differentiation sequence reached higher degrees of fractionation at a regional scale. Although crystal fractionation played an important role, late-stage fluid/melt interactions, involving F-rich fluids, imparted specific geochemical characteristics to Macao and SE China highly fractionated granitic rocks such as the non-CHARAC (CHArge-and-RAdius-Controlled) behavior of trace elements, leading, for example, to non-chondritic Zr/Hf ratios, Rare Earth Elements (REE) tetrad effects and Nb-Ta enrichment and fractionation. Such process contributed to the late-stage crystallization of accessory phases only found in these highly evolved facies. Among the latter, two populations of garnet were identified in MGI (Macao Group I) highly fractionated granitic rocks: small grossular-poor euhedral grains and large grossular-rich skeletal garnet grains with quartz inclusions. The first group was mainly formed through precipitation from highly evolved Mn-rich slightly peraluminous melts under low-pressure and relatively low temperature (∼700 °C) conditions. Assimilation of upper crust metasedimentary materials may have contributed as a source of Mn and Al to the formation of garnet. The second group has a metasomatic origin related to the interaction of magmatic fluids with previously crystallized mineral phases and, possibly, with assimilated metasedimentary enclaves or surrounding metasedimentary strata. The highly fractionated granitic rocks in Macao represent the first stage in the development of granite-related W-(Mo)-Sn-Nb-Ta mineralization associated with coeval more evolved lithotypes in SE China.
1 citations (Crossref) [2022-09-21]

MaGIC – Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China. - Dias, Ágata (University of Saint Joseph, 2017)

Hydrothermal remobilization of subseafloor sulfide mineralization along mid-ocean ridges contributes to the global oceanic zinc isotopic mass balance - Liao, Shili; Tao, Chunhui; Wen, Hanjie; Yang, Weifang; Liu, Jia; Jamieson, John W.; Dias, Ágata Alveirinho; Zhu, Chuanwei; Liang, Jin; Li, Wei; Ding, Teng; Li, Xiaohu; et al. (Geochimica et Cosmochimica Acta, 2022)
Hydrothermal activity on mid-ocean ridges is an important mechanism for the delivery of Zn from the mantle to the surface environment. Zinc isotopic fractionation during hydrothermal activity is mainly controlled by the precipitation of Zn-bearing sulfide minerals, in which isotopically light Zn is preferentially retained in solid phases rather than in solution during mineral precipitation. Thus, seafloor hydrothermal activity is expected to supply isotopically heavy Zn to the ocean. Here, we studied sulfide-rich samples from the Duanqiao-1 hydrothermal field, located on the Southwest Indian Ridge. We report that, at the hand-specimen scale, late-stage conduit sulfide material has lower δ66Zn values (−0.05 ± 0.15 ‰; n = 19) than early-stage material (+0.13 ± 0.15 ‰; n = 10). These lower values correlate with enrichments in Pb, As, Cd, and Ag, and elevated δ34S values. We attribute the low δ66Zn values to the remobilization of earlier sub-seafloor Zn-rich mineralization. Based on endmember mass balance calculations, and an assumption of a fractionation factor (αZnS-Sol.) of about 0.9997 between sphalerite and its parent solution, the remobilized Zn was found consist of about 1/3 to 2/3 of the total Zn in the fluid that formed the conduit samples. Our study suggests that late-stage subsurface hydrothermal remobilization may release isotopically-light Zn to the ocean, and that this process may be common along mid-ocean ridges, thus increasing the size of the previously identified isotopically light Zn sink in the ocean.
Keywords: Hydrothermal activity; Mid ocean ridge; Subsurface remobilization; Zinc isotopic mass balance

Hydrothermal Fe-Mn deposits from low-temperature systems of the Mid-Atlantic Ridge - Costa, P; Dias, Ágata (2019)

High-precision geochronology of Mesozoic magmatism in Macao, Southeast China: Evidence for multistage granite emplacement - Quelhas, Pedro; Dias, Ágata; Mata, João; Davis, Donald Wayne; Ribeiro, Maria Luísa (Geoscience Frontiers, 2020)
5 citations (Crossref) [2022-09-21]

Geology of the Macao Special Administrative Region (China) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João (Journal of Maps, 2021)
A 1:12,000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies.
0 citations (Crossref) [2022-09-21] Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/17445647.2021.1906340
Keywords: Jurassic; Macao (South China); Mesozoic; geological map; granites; magmatic rocks

Geological Map of the Macao Special Administrative Region (China) - Quelhas, P; Borgens, R; Dias, Ágata; Ribeiro, L; Costa, P; Mata, J (Journal of Maps, 2021)
0 citations (Crossref) [2022-09-21]

Geochronological, geochemical and petrographic constraints on incremental pluton growth: the case of Macao granitic suite - Dias, Ágata; Quelhas, P; Mata, J; Wayne, Davis (2019)

Geochemistry, sulfur and lead isotopic composition of hydrothermal sulfide from the Duanqiao hydrothermal field on the Southwest Indian Ridge: implications for ore genesis - Yang, Weifang; Liao, Shili; Alveirinho Dias, Ágata; Liang, Jin; Li, Wei; Ding, Teng; Tao, Chunhui (International Geology Review, 2022)
Hydrothermal activities on ultraslow-spreading ridges exhibit diverse characteristics, long histories with multiple participants, and might form large-scale, high-grade sulfide deposits. The Duanqiao hydrothermal field (DHF) is located at the segment with the thickest oceanic crust and a large axial magma chamber on the Southwest Indian Ridge, providing unique perspective of sulfide metallogenesis on ultraslow-spreading ridges. Previous studies revealed that DHF sulfide exhibits distinct features of enrichment of ore-forming elements in comparison with those of hydrothermal fields on sediment-starved mid-ocean ridges. However, the genesis and processes responsible for such differences remain poorly constrained. In this study, mineralogical, geochemical and S and Pb isotopic analyses were performed on relict sulfide mound samples to characterize DHF formation. The samples show clear concentric mineral zonation from the interior to the exterior wall. Assemblages of chalcopyrite, sphalerite, and pyrite are distributed mainly in the interior wall, whereas pyrite and marcasite are distributed mainly in the exterior wall. The low Cu content and Pb isotopic composition of the sulfide indicate that the metals are derived mainly from basement basalts. The δ34S values exhibit positive values distributed over a reasonably narrow range (2.42‰–7.97‰), which suggests approximately 62.1%–88.5% of S with basaltic origin. Compared with most hydrothermal fields along the sediment starved mid-ocean ridges, the DHF sulfide shows particularly high contents of Pb (263–2630 ppm), As (234–726 ppm), Sb (7.32–44.3 ppm), and Ag (35.2 to >100 ppm). The δ34S values exhibit an increasing tendency from the sample exterior to the interior. We propose that these features probably reflect the existence of a subsurface zone refining process. Our results provide new insight into the sulfide formation process and contribute to understanding the metallogenic mechanism of hydrothermal sulfides on ultraslow-spreading ridges.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/00206814.2022.2081937
Keywords: Hydrothermal sulfide; geochemistry; southwest Indian ridge; sulfur isotope; zone refining

Geochemistry of Fe-Si-(Mn) Chimneys from Luso Vent Field, MAR - Dias, Ágata; Costa, P; Marques, A F; Ribeiro, L; Madureira, P; Calado, A; Gonçalves, E; Morato, T (2019)

Geochemistry and stable isotope constraints on high-temperature activity from sediment cores of the Saldanha hydrothermal field - Dias, Ágata; Früh-Green, G.L.; Bernasconi, S.M.; Barriga, F.J.A.S. (Marine Geology, 2011)
24 citations (Crossref) [2022-09-21]

Geochemical and mineralogical investigations of seafloor oxyhydroxides deposits collected in Mid-Atlantic Ridge hydrothermal fields - Costa, P; Dias, Ágata

Evidence for mixed contribution of mantle and lower and upper crust to the genesis of Jurassic I-type granites from Macao, SE China - Quelhas, Pedro; Mata, João; Dias, Ágata (GSA Bulletin, 2021)
Abstract Much controversy has occurred in the past few decades regarding the nature of the sources, the petrogenetic processes, and the tectonic regime(s) of the Jurassic magmatism within the Southeast China magmatic belt. This study aims to contribute to the discussion with mineral chemistry, and whole-rock element and Sr-Nd-Hf-Pb isotopic geochemical data from granitic rocks and microgranular mafic enclaves from Macao, where two discrete groups of I-type biotite granites have been identified (referred to as Macao Group I [MGI] and Macao Group II [MGII]). It is proposed that the granitic magmas were generated by partial melting of infracrustal medium- to high-K, basaltic Paleoproterozoic to Mesoproterozoic protoliths (Nd depleted mantle model age [TDM2] = 1.7–1.6 Ga and Hf TDM2 = 1.8–1.6 Ga), triggered by underplating of hot mantle-derived magmas in an extensional setting related to the foundering of a previously flat slab (paleo–Pacific plate) beneath the SE China continent. The main differences between the two groups of Macao granites are attributed to assimilation and fractional crystallization processes, during which upper-crustal Paleozoic metasediments were variably assimilated by MGI magmas. This is evidenced by an increase in initial 87Sr/86Sr ratios with degree of evolution, presence of metasedimentary enclaves, and high percentage of zircon xenocrysts with Paleozoic ages. In addition, other processes like late-stage fluid/melt interaction and magma mixing also left some imprints on granite compositions (rare earth element tetrad effect plus non–charge-and-radius-controlled behavior of trace elements and decoupling between different isotope systems, respectively). The distribution of isotopically distinct granites in SE China reflects the nature of the two Cathaysia crustal blocks juxtaposed along the Zhenghe-Dapu fault.
7 citations (Crossref) [2022-09-21]

Diving into the unknown: robotics as tools to study the deep-sea. Informed Scientific Sampling in Large-scale Outdoor Environments - Dias, Ágata (2019)

A origem e evolução dos magmas graníticos de Macao à luz de dados de geoquímica elementar e isotópica / Source and evolution of Macao granitic magmas: insights from wholerock geochemistry and isotopic signatures. - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Ribeiro, M L; Borges, R (2018)